Analysis of the Causes of Elementary School Students' Difficulties in Learning Mathematics: A Qualitative Study - Ulfa, Sofia (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2026)
This study aims to analyze the underlying causes of elementary school students’ difficulties in learning mathematics through a qualitative research approach. Mathematics is a foundational subject, yet many students experience persistent challenges that affect their academic performance and long-term numeracy development. Using a qualitative descriptive design, this research involved interviews, classroom observations, and document analysis of 28 students and 4 teachers from two public elementary schools. The data were coded and categorized into themes to capture patterns of difficulties and contributing factors. The findings reveal several dominant causes, including limited conceptual understanding, low mathematical confidence, ineffective instructional strategies, and inadequate learning support at home. Additional difficulties were linked to linguistic barriers, poor number sense, and anxiety triggered by traditional assessment practices. The study also identified environmental influences such as classroom overcrowding and inconsistent teacher feedback as significant contributors. These findings provide a comprehensive understanding of the multifaceted challenges faced by students and highlight the importance of adopting student-centered instructional approaches, strengthening teacher pedagogical competence, and improving parental engagement. The implications emphasize the need for tailored interventions to address conceptual, psychological, and environmental factors that hinder mathematical learning at the elementary level.